A Review on Coronaviruses: The Infectious Agent to Animals and Human - NiLuh Putu Indi Dharmayanti; Diana Nurjanah (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2020)
Coronavirus is a non-segmented, positive-stranded RNA virus with four main structural proteins, namely Spike (S), Membrane (M), Envelope (E), and Nucleocapsid (N) proteins. Coronavirus can cause diseases in the respiratory and digestive tract, as well as in central nervous system of animals and humans. There are four genera in the Orthocoronavirinae subfamily, including Alphacoronavirus, Betacoronavirus, Gammacoronavirus, and Deltacoronavirus. Alphacoronavirus and Betacoronavirus are commonly found in mammals, while Gammacoronavirus and Deltacoronavirus are found to infect  birds and mammals. Until 2018, zoonoses coronaviruses consisted of SARS-CoV and MERS-CoV. Coronavirus became worldwide concern after it was identified as the cause of the pneumonia outbreak occurred at the end of 2019 in China. The coronavirus is associated with the fish market in Wuhan, then the disease is called COVID-19 (Coronavirus Infectious Diseases-19) caused by SARS-CoV-2. Virus SARS-CoV-2 has infected >1.6 million people around the world and until the end of March 2020, it caused more than 99.000 deaths including 3.512 cases with the total number of deaths to 306 in Indonesia. This paper discusses Coronavirus and scientific information related to Coronaviruses in which several variants are zoonoses.